The Effect of Different Water Sources on Growth and Survival Rate Of BaungFish(Hemibagrus nemurus) - Nainggolan, Evy Purnama; M Tang, Usman; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             Thisresearch was conducted on 24 November until 22 December 2018 at Aquaculture Technology Laboratory of Fisheries and Marine, University Riau, Pekanbaru. The purpose of thisDifferent Water Sources on Growth and Survival Rate Of  Baung Fish (Hemibagrus nemurus). The research method use in this study was an experimental method and completely randomized design with three treatments and five replication. The treatments in this study were 1=peat water, 2=clean water, 3=green water. The results showed treatment 3= green water. Absolute weight growth of 1,34 g, growth of absolute length 1,64 cm, daily growth rate of 0,031%, and survival rate of 100%. Keywords:Water Sources, baung fish, Growth